A Study on Chewable Tablets for the Anti-Allergic Drug - Subhash Tarate, Mr. Vivek; Pati, Dr. Jagdishchandra (Journal of Biomedical and Pharmaceutical Research, 2023)
Abstract: According to this theory, the interface between the layers should fuse together during compaction and be strongly held together following tablet ejection by adhesion forces. This is not always the case, and since the individual layers’ compressibility and compact ability shouldn’t be the reason for delamination, it is necessary to find other physical mechanisms that might explain the issues with delamination. Stability experiments were conducted on the improved dosage form formulations to identify physical and chemical changes that occurred during storage. On storage, the improved formulation’s physicochemical property did not change considerably. the few alterations in in vitro release that were seen both before and after preservation. According to the outcome, the formulation was stable under the necessary storage conditions.